Strengthening Nutrition Sources Based on Local Food as an Effort to Prevent Stunting - Dhita Yuniar Kristianingrum; Baroroh Barir; Siti Shofiyah; Esti Pratiwi Yosin; Devi Fitria Sandi (Jurnal Penelitian Pendidikan IPA, 2023)
This short study aims to illustrate how the power of local food as a source of community nutrition is very adequate. This study focuses on the sexy national issue of stunting in children who should be experiencing perfect growth and development. The research method in this study is a discourse search and analysis with a content analysis approach of a scientific work. The study will be described with a narrative that has been qualitatively analysis based on certain categories. Data sources are various scientific journals, reference books and other sources considered compatible with this study. The use of local food potential to be empowered into processed food is very likely to be used as food to prevent stunting symptoms in infant growth. From this study, it can be concluded that various studies confirm how the contribution of local resources in terms of food is very significant in helping the stunting reduction program in the community. The nutritional content contained in corn, sweet potatoes, taro, carrots, tubers and so on are very contributive alternative ingredients. As an example, children who are lacking in vitamin C will have difficulty in forming protein and collagen, which will inhibit their growth and development. Normal children's protein intake was mostly from animal-source foods such as eggs, but the protein intake of stunted children was primarily sourced from legumes